2005
DOI: 10.1248/bpb.28.2155
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Constituents of Galla Rhois with Hepatoprotective Effects on Tacrine- and Nitrofurantoin-Induced Cytotoxicity in Hep G2 Cells

Abstract: The bioassay-guided fractionation of the MeOH extract of Galla Rhois furnished two hepatoprotective compounds, an equilibrium mixture of 3-galloyl-gallic acid and 4-galloyl-gallic acid isomers (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…As an antiviral, RC ethyl acetate extract has inhibitory effects against hepatitis carcinoma virus [29,30] and severe acute respiratory syndrome corona virus [30]. Penta-1,2,3,4,6-O-galloyl-β-D-glucose (PGG) isolated from RC shows promising hepatoprotective properties [31] and the anticancer effects of RC are believed to involve inhibition of dcd25A phosphotase activity [32] or gallic acid as one of the bioactive components in RC [26,33,34] which directly induces apoptosis in prostate cancer cells [35]. PGG was also shown by Huh et al, to be a constituent in RC with ability to inhibit angiogenesis and stimulate apoptosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…As an antiviral, RC ethyl acetate extract has inhibitory effects against hepatitis carcinoma virus [29,30] and severe acute respiratory syndrome corona virus [30]. Penta-1,2,3,4,6-O-galloyl-β-D-glucose (PGG) isolated from RC shows promising hepatoprotective properties [31] and the anticancer effects of RC are believed to involve inhibition of dcd25A phosphotase activity [32] or gallic acid as one of the bioactive components in RC [26,33,34] which directly induces apoptosis in prostate cancer cells [35]. PGG was also shown by Huh et al, to be a constituent in RC with ability to inhibit angiogenesis and stimulate apoptosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of natural hepatoprotective agents have revealed that the extract of Galla chinensis showed promising hepatoprotective activity Tian et al, 2005). Based on an activity-guided separation scheme An et al (2005) purifi ed pentagalloylglucose [1] and an equilibrium mixture of 3-galloyl-gallic acid and 4-galloyl-gallic acid isomer from the methanol extract of Galla chinensis and validated their hepatoprotective activity. Pentagalloylglucose [1] and the mixture compounds were found to have marked protective effects on tacrine-induced cytotoxicity in human liver-derived Hep G2 cells with EC 50 values of 70.39 ± 5.4 and 29.51 ± 0.7 μm, respectively, and also inhibited nitrofurantoininduced cytotoxicity in Hep G2 cells at 150.9 ± 6.4 and 23.81 ± 0.5 μm respectively.…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…Equilibrium mixture of ethyl m-digallate and ethyl p-digallate isomers (EDG) and gallic acid (GA) were isolated from ethanol extract of Galla Rhois through bioassay-guided fractionation, as described by An et al, 2005 and its chemical structure is shown in Fig. 1 …”
Section: Preparation Of Edg and Gamentioning
confidence: 99%